New Geometric Models for Shape Quantification of the Dorsal View in Seeds of Silene Species - Rodríguez-Lorenzo, José Luis; Martín-Gómez, José Javier; Tocino, Ángel; Juan, Ana; Janoušek, Bohuslav; Cervantes, Emilio (Plants (Basel, Switzerland), 2022)
The description of shape in Silene seeds is based on adjectives coined by naturalists in the 19th century. The expressions reniform, dorso plana, and dorso canaliculata were applied in reference to lateral or dorsal views of seeds, but the characters described can be submitted now to an analytical description by quantitative methods, allowing shape quantification and the comparison between species or populations. A quantitative morphological analysis is based on the comparison with geometric models that adjust to the shape of seeds. Morphological analysis of the dorsal view of Silene seeds based on geometric models is applied here to 26 seed populations belonging to 12 species. According to their dorsal views, the seeds are classified as convex and non-convex. New geometric models are presented for both types, including figures such as super-ellipses and modified ellipses. The values of J index (percent of similarity of a seed image with the model) are obtained in representative seed samples from diverse populations and species. The quantitative description of seed shape based on the comparison with geometric models allows the study of variation in shape between species and in populations, as well as the identification of seeds in Silene species. The method is of application to other plant species.
Keywords: convexity; oval; model; symmetry; super-ellipse; cardioid; morphology; seed shape; geometry